2013
DOI: 10.1002/ajmg.a.36243
|View full text |Cite
|
Sign up to set email alerts
|

WNT10A mutations account for ¼ of population‐based isolated oligodontia and show phenotypic correlations

Abstract: A large proportion (>50%) of patients with isolated oligodontia were recently reported with WNT10A mutations. We have analyzed a population-based cohort of 102 individuals diagnosed with non-syndromic oligodontia and a mean of 8.2 missing teeth. The cohort included 94 families and screening of WNT10A identified that 26 probands (27.7%) had at least one WNT10A variant. When we included the MSX1, PAX9, AXIN2, EDA, EDAR, and EDARADD genes, 38.3% of probands were positive for a mutation. Biallelic WNT10A mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 29 publications
12
53
2
1
Order By: Relevance
“…None of the patients presented with the typical phenotype of EDA - or EDAR -induced hypohidrotic ED [24, 25] and the ectodermal signs and symptoms were incongruous with any defined ED-entity. The spectrum of ectodermal symptoms among our seven patients is consistent with that previously reported in patients with bi-allelic WNT10A mutations [36, 8, 10], and even in some patients with mono-allelic mutations [4, 6, 8, 11, 12]. Notably, with the exception of tooth agenesis, the signs and symptoms from ectodermal appendages in a majority of individuals in our cohort were subtle and in several cases even not experienced as abnormal by the study persons or their parents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…None of the patients presented with the typical phenotype of EDA - or EDAR -induced hypohidrotic ED [24, 25] and the ectodermal signs and symptoms were incongruous with any defined ED-entity. The spectrum of ectodermal symptoms among our seven patients is consistent with that previously reported in patients with bi-allelic WNT10A mutations [36, 8, 10], and even in some patients with mono-allelic mutations [4, 6, 8, 11, 12]. Notably, with the exception of tooth agenesis, the signs and symptoms from ectodermal appendages in a majority of individuals in our cohort were subtle and in several cases even not experienced as abnormal by the study persons or their parents.…”
Section: Discussionsupporting
confidence: 91%
“…Genetic analysis of exons and their flanking sequences of WNT10A was performed as described previously [11], and the results revealed bi-allelic mutations in all seven individuals. All parents were found to be heterozygous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotype-phenotype analysis of individuals with WNT10A mutations by our previous study and others revealed that premolars were the most commonly missing teeth (62.5%-68.8%), whereas incisors were missing only 18.8%-31.3% of the time. 8,31,32 In contrast, the most frequently missing permanent teeth in the affected individuals with WNT10B variants were the lateral incisors (83.3%; Table 1), whereas premolars were missing only 51.4% of the time, a pattern clearly different from the oligodontia patterns resulting from WNT10A mutations. Given that the most commonly affected teeth in DPSCs were isolated and cultured as described in our previous study.…”
mentioning
confidence: 94%